Design of 4.7 μm High-Efficiency Hybrid Dielectric Reflection Gratings - Ye Wang (Micromachines, 2022)
Traditional reflective diffraction gratings working at 4.7 μm are fabricated by metal coatings. Due to the absorption of the metal itself, the diffraction efficiency (DE) could not reach over 95%. In this paper, we propose a 3 μm period multilayer grating design using hybrid multilayer dielectrics. With a layer of 0.353 μm Si and a layer of 0.905 μm SiO2 forming the rectangular grating, the maximum of larger than 99.99% and the overall first-order DE reached 97.88%. The usable spectrum width is larger than 0.2 μm, more than four times larger than that of the pure Si rectangular grating. This high DE multilayer grating is an ideal element for high-power laser systems with the spectrum beam combining method.